Development of Creative Abilities of Students Using the Project Method in Technical Universities (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A specific feature of project activity is its activating influence on the development of the creative orientation of the individual and ensuring the creative nature of mastering reality. The article discusses project activities that provide the student with a wide field of new activities, contributing to the formation of a creative, self-confident, proactive personality, capable of working individually and in a team, capable of learning throughout life.